Low cost bifunctional initiators for bidirectional living cationic polymerization of olefins. II. hyperbranched styrene–isobutylene–styrene triblocks with superior combination of properties. Issue 7 (26th December 2017) - Nugay, Nihan; Nugay, Turgut; Deodhar, Tejal; Keszler, Balazs L.; Kennedy, Joseph P.
ABSTRACT: Both bifunctional initiators, the new low cost bBCB‐diCl [4, 9‐dichloro, 2, 4, 7, 9‐tetramethyl‐tricyclo[6.2.0.0 36 ]deca‐1(8), 2, 6‐triene] and the universally used "hindered" HDCCl [1‐( tert ‐butyl)‐3, 5‐bis(2‐chloropropan‐2‐yl)benzene] induce the living bidirectional block copolymerization of isobutylene (IB) followed by styrene (St), and produce PSt‐ b ‐PIB‐ b ‐PSt (SIBS) triblocks. We discovered that the molecular weights of triblocks kept significantly increasing long after St conversion reached completion during syntheses. Results were explained by the formation of blends consisting of the expected linear SIBS plus hyperbranched SIBS, HB(SIBS) n . The structure of high molecular weight (>10 6 g/mol) HB(SIBS) n was characterized by various techniques, and key properties of SIBS/HB(SIBS) n blends were investigated. The mechanism of HB(SIBS) n formation and the synthesis of SIBS/HB(SIBS) n blends was elucidated. The properties of SIBS/HB(SIBS) n blends are superior to those of SIBS. Thus, whereas SIBS exhibits ∼25 MPa tensile strength and ∼450% elongation, SIBS/HB(SIBS) n blends exhibit 25–27 MPa tensile strength and >400% elongation; deformation under constant load of SIBS is ∼12%, whereas that of SIBS/HB(SIBS) n is <1%; permanent set of SIBS is 1.3% whereas that of SIBS/HB(SIBS) n is <0.5%. SIBS/HB(SIBS) n blends also exhibit higher yield, yield strength, and toughness than SIBS. The microstructure/property relationship of HB(SIBS) n is discussed and the reasons for enhanced properties of SIBS/HB(SIBS) n blends are analyzed. © 2017 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2018, 56, 705–713 Abstract : Bidirectional living polymerization of isobutylene followed by styrene produces poly(styrene‐ b ‐isobutylene‐ b ‐styrene) (SIBS) thermoplastic elastomers. Extending the blocking time of styrene a few hours after complete styrene conversion produces blends of SIBS plus hyperbranched SIBS, HB(SIBS) n . These blends exhibit excellent mechanical properties including superior strength, elongation, modulus, toughness, extremely low creep (<1.0%) and permanent deformation (<0.5%). The sketch helps to visualize the likely microstructure of SIBS/HB(SIBS) n blends.